Impact of daclizumab versus interferon beta-1a on patient-reported outcomes in relapsing-remitting multiple sclerosis - Liu, Ying; Vollmer, Timothy; Havrdova, Eva; Riester, Katherine; Lee, Andrew; Phillips, Glenn; Wang, Ping; Sabatella, Guido (Multiple sclerosis and related disorders, 2017)
BACKGROUND: Patient-reported outcomes (PROs) provide information on treatment effects from the patient's perspective that complement outcomes on clinical measures. In DECIDE, daclizumab demonstrated superior efficacy in reducing relapses, 24-week confirmed disability progression, and brain lesions (assessed by magnetic resonance imaging [MRI]) versus intramuscular interferon beta-1a in relapsing-remitting multiple sclerosis. OBJECTIVE: To examine the impact of daclizumab versus interferon beta-1a on PROs in DECIDE. METHODS: DECIDE was a randomized, double-blind, active-controlled, phase 3 study comparing daclizumab 150mg subcutaneous every 4 weeks with interferon beta-1a 30mcg intramuscular once weekly. The 29-item Multiple Sclerosis Impact Scale (MSIS-29) and EuroQoL 5-Dimensions (EQ-5D) were assessed at baseline and every 24 weeks. Mean changes from baseline were analyzed using analysis of covariance models. Individual items for the MSIS-29 physical (PHYS) and psychological (PSYCH) subscales were analyzed post hoc. RESULTS: Daclizumab treatment resulted in greater mean improvements relative to baseline in MSIS-29 PHYS and PSYCH scores starting at week 24 that persisted over 96 weeks. Mean improvements from baseline in MSIS-29 PHYS and PSYCH scores were significantly greater for daclizumab versus intramuscular interferon beta-1a at week 96. Daclizumab-treated patients showed steady improvements in EQ-5D health utility index and EQ-5D visual analog scale scores over the study period, with significantly greater improvements versus intramuscular interferon beta-1a at week 96 (p=0.0048 and p=0.0006, respectively). CONCLUSIONS: Improvements in patient-reported physical and psychological functioning and general health status with daclizumab compared with intramuscular interferon beta-1a are consistent with outcomes on clinical and brain MRI lesion measures in DECIDE (NCT01064401).
Keywords: hodnocení výsledků péče pacientem; Relapsing-remitting; Humans; Patient Reported Outcome Measures; Patient-reported outcomes; lidé středního věku; imunoglobulin G; Double-Blind Method; mladý dospělý; dospělí; dvojitá slepá metoda; humanizované monoklonální protilátky; daklizumab; lidé; Daclizumab; mladiství; časové faktory; Adult; Multiple sclerosis; imunologické faktory; Antibodies, Monoclonal, Humanized; Multiple Sclerosis, Relapsing-Remitting; relabující-remitující roztroušená skleróza; Middle Aged; Adolescent; Immunologic Factors; Young Adult; Immunoglobulin G; Time Factors; Interferon beta-1a; interferon beta 1a